Indiana Jones and the kingdom of the crystal skull [videorecording (Blu-Ray)] - Ford, Harrison, 1942-; LaBeouf, Shia, 1986-; Blanchett, Cate, 1969-; Spielberg, Steven, 1946- (Paramount, 2008)
Archaeologist Jones teams up with former flame Marion and her hot-headed son to rescue an old friend from the Soviets.